Answer:
1. P =
![(I)/(rt)](https://img.qammunity.org/2022/formulas/mathematics/college/7x2m07a1nkjcudd8sf0r1eylp5achwotry.png)
2. y =
or
(depending on how you want the equation arranged)
3. c =
![(a-bd)/(b)](https://img.qammunity.org/2022/formulas/mathematics/college/se3oijlxr9fc3lhjw48w1q37qv3r0gp9n6.png)
4 t =
![(A - p )/(pr)](https://img.qammunity.org/2022/formulas/mathematics/college/h2hoedfizwltt5zq7tg6xdg0m6v2k0taof.png)
Explanation:
1. I =Prt for P:
I = Prt divide both sides by rt to isolate P
P =
![(I)/(rt)](https://img.qammunity.org/2022/formulas/mathematics/college/7x2m07a1nkjcudd8sf0r1eylp5achwotry.png)
2. 3x + 11y = 6 for y
3x + 11y = 6 subtract 3x from both sides
11y = 6 - 3x divide both sides by 11
y =
or
depending on how you want the equation arranged
3. a = b(c + d) for c
a = b(c + d) distribute b to (c+d)
a = bc + bd subtract bd from both sides
a - bd = bc divide both sides by b
c =
![(a-bd)/(b)](https://img.qammunity.org/2022/formulas/mathematics/college/se3oijlxr9fc3lhjw48w1q37qv3r0gp9n6.png)
4. A = p + prt for t
A = p + prt subtract p from both sides
A - p = prt divide both sides by pr
t =
![(A - p )/(pr)](https://img.qammunity.org/2022/formulas/mathematics/college/h2hoedfizwltt5zq7tg6xdg0m6v2k0taof.png)